SELECTION OF FUNGAL ISOLATES WITH POTENTIAL FOR PHOSPHATE SOLUBILIZATION AND FORMULATION OF INOCULANT FOR COFFEE CROPS - Chalfoun, Sara Maria; Angélico, Caroline Lima; de Resende, Mário Lúcio Vilela; de Moraes, Graziella Evaristo (Coffee Science - ISSN 1984-3909, 2019)
The dependence on chemical fertilizers for the future of agriculture will result in additional soil health losses, possibility of water contamination and continued currency avoidance due to the increasing dependence on imports. The indiscriminate use of synthetic fertilizers has polluted the soil and watersheds, destroying useful microorganisms and insects, what makes crops more susceptible to diseases. Considering this critical scenario, microorganisms have stood out as a potential alternative for maintaining the productivity, reliability and sustainability of the global food chain. In order to increase the productivity and/or reduce the amount of fertilizers, as well as to meet the requirements for the use of low-solubility phosphorus sources, microorganisms were isolated from the rhizosphere and artificially cultivated. Subsequently, they were selected regarding their potential for solubilizing phosphorus and incorporated into a low-cost matrix. A microbial inoculant was thus developed and tested in a coffee crop. It was possible to formulate an inoculant based on an isolate selected from Aspergillus niger, using an inactivated seed and sodium alginate as matrices. It was also observed that there was a greater correlation between the evaluated parameters and increasing doses of the inoculants when Araxá apatite was used as source of phosphorus, proving the importance of the inoculants as release factors and availability of phosphorus in the case of sources less soluble, giving Brazilian agriculture greater autonomy in the input market.